The Effect Of Work Discipline, Organizational Commitment and Competency On The Performance Of Novotel Pekanbaru Hotel Employees - Nadia Karima; Dewita Suryati Ningsih; Ahmad Rifqi (INTERNATIONAL JOURNAL OF ECONOMICS, BUSINESS AND APPLICATIONS, 2022)
This study aims to determine the effect of work discipline, organizational behavior, and competence on employee performance. This research was conducted at the Novotel Hotel Pekanbaru. The research population in this study was the Novotel Hotel employees, numbering as many as 135 people. The research sample was taken from as many as 57 people using the Slovin formula, for a total sample of 57 people. The data collection method used in this study was a questionnaire about work discipline, organizational behavior, and performance competence, which was then analyzed using multiple linear regression. The results of this study are that: (1) there is a significant effect of work discipline on employee performance. This means that the higher the employee's work discipline, the higher the performance of the Novotel Pekanbaru Hotel employees. (2) There is an effect of organizational commitment on employee performance. This means that the higher the employee's organizational commitment, the higher the performance of the Novotel Pekanbaru Hotel employees. (3) Employee competence has an impact on the performance of Novotel Hotel employees. This means that the higher an employee's competence, the better their performance. (4) Simultaneously, there is a significant influence between work discipline, organizational commitment, and employee competence on the performance of Novotel Pekanbaru Hotel employees.